Implementasi Penanaman Pendidikan Karakter Dalam Pembelajaran IPS Melalui Penayangan Video Sejarah Kemerdekaan Untuk Siswa Kelas 5 Sekolah Dasar Negeri 2 Saptorenggo - Achmad Chusairi; Oktaviani Adhi Suciptaningsih (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2023)
The purpose of this research is to look at character education in social studies learning in the video showing the history of independence. The method used in this research is using qualitative descriptive. In a qualitative descriptive method, researchers do not use statistics in data analysis because the data collected is descriptive or narrative in nature. In addition, this method also pays attention to the context and experience of the subject being researched, so as to be able to provide a more detailed and in-depth picture of the phenomenon being studied. In this study students felt very enthusiastic and enthusiastic in participating in learning because students were more interested in delivering material using digital-based media. Students are able to clearly state what characters appear and can tell the plot presented from the presentation of the history of the independence of the Indonesian nation in social studies learning.